Future Challenges in Southern Ocean Ecology Research - Xavier, José C.; Brandt, Angelika; Ropert-Coudert, Yan; Badhe, Renuka; Gutt, Julian; Havermans, Charlotte; Jones, Christopher; Costa, Erli S.; Lochte, Karin; Schloss, Irene R.; Kennicutt, Mahlon C.; Sutherland, William J. (Frontiers in Marine Science, 2016)
The Southern Ocean is experiencing relentless change. The Antarctic and Southern Ocean community, represented by 75 scientists and policy-makers from 22 countries, recently met to formulate a collective vision on the priorities for Antarctic research for the next two decades and beyond. Here, we assess high-interest research areas related specifically to Southern Ocean life and ecology that, although not all retained as the 80 top priorities among the addressed scientific domains, are of considerable relevance to the biology and ecology of the Southern Ocean. As certain regions of the Southern Ocean ecosystems have witnessed abiotic and biotic changes in the last decades (e.g. warming, changes in sea ice and abundance of marine organisms), such an exercise was urgently needed. We concluded that basic biological information on the taxonomy of numerous organisms is still lacking in areas such as the deep-ocean floor or the under-ice environments. Furthermore, there is a need for knowledge about the response and resilience of Antarctic marine ecosystems to change. The continuation of a long-term commitment and the development and use of innovative technology to adequately monitor the Southern Ocean ecosystems is required. Highlighting the most important Southern Ocean research topics allow the identification of the challenges and future requirements in technological development, and both research and funding strategies for the various stakeholders